2014
DOI: 10.5152/iao.2014.64
|View full text |Cite
|
Sign up to set email alerts
|

The Caloric Test and the Video Head-Impulse Test in Patients with Vertigo

Abstract: OBJECTIVE:The caloric test and the video head-impulse test are diagnostic tools that examine the function of the horizontal semicircular canal. There are major differences between the two tests. These are stimulus characteristics, methodology, and function examined. MATERIALS and METHODS:This is a prospective work in 123 patients with different types of vestibular disease seen because of dizziness in which both procedures were performed the same day. First, the spontaneous nystagmus and head-shake nystagmus we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 12 publications
2
29
0
1
Order By: Relevance
“…These results were also important in the context of interpreting VHIT results that were not previously clear cut or unambiguous. Many authors have reported cases where patients with abnormalities found using sinusoidal tests gave normal VHIT results [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…These results were also important in the context of interpreting VHIT results that were not previously clear cut or unambiguous. Many authors have reported cases where patients with abnormalities found using sinusoidal tests gave normal VHIT results [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…The test is objective and reliable that can assess vertical and horizontal semicircular canals [8]. The subjective bed side HIT has some drawbacks in which there is no quantitative estimation of the extent of VOR gain and it is a purely subjective estimation of the clinician.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because the disease is in another part of the inner ear (as in the case of patients with BPPV) or because it does not strike in the inner ear (as in some cases of chronic subjective dizziness) and it could be cases with vestibular migraine, cervicogenic vertigo, sacular disorders and systemic causes [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For establishing a necessary topodiagnostic procedure, we are using a neurotological history scheme, audiometry, computer-based electronystagmography with caloric and optokinetic tests, and VHIT [2] along with evaluating speech audiometry and evoked responses. Based on the literature, VEMP (either cervical or ocular) did not show any use in MD [3].…”
Section: Introductionmentioning
confidence: 99%